MELATIH RELAKSASI NAFAS DALAM UNTUK PENURUNAN NYERI AKUT PADA PENDERITA INFEKSI SALURAN KEMIH - Julita, Sri; Afrilia, Putri; Batubara, Khairunnisa (LPPM AKPER GITA MATURA ABADI KISARAN, 2025)
Urinary tract infection is a disease that attacks the urinary tract in the kidneys, ureters, bladder, or urethra caused by the spread of bacterial infection. This condition generally causes pain. Deep breathing relaxation is one of the non-pharmacological therapies to overcome pain. This scientific paper is used to implement deep breathing relaxation techniques in patients with urinary tract infections with acute pain problems. The method used in compiling this case is a descriptive method, namely providing an overview of the health and nursing problems faced by patients with urinary tract infections. The results of the study after administering deep breathing techniques to the first patient showed a decrease in pain with an initial scale of 4-6 until the patient did not feel pain. And the second patient with a pain scale of 6-7 until there was no more pain, so it can be concluded that this deep breathing technique has an effect on reducing pain. It can be concluded that the deep breathing relaxation technique taught to patients can reduce the level of pain experienced by patients with urinary tract infections.